Which is better for durable goods producers, exclusive or open supply chain? - Hiroshi Kitamura; Noriaki Matsushima; Misato Sato (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We explore the supply chain problem of a downstream durable goods monopolist, who chooses one of the following trading modes: an exclusive supply chain with an incumbent supplier or an open supply chain, allowing the monopolist to trade with a new efficient entrant in the future. The predicted retail price reduction in the future dampens the profitability of the original firms. An efficient entrant's entry magnifies such a price reduction, causing a further reduction of original firms' joint profits. In equilibrium, the downstream monopolist chooses the exclusive supply chain to escape further price reductions, although it anticipates efficient entry.
Keywords: L12; L41; L42; 330; Antitrust policy; Durable goods; Exclusive supply chain; Vertical relation